The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0149206319864155
|View full text |Cite
|
Sign up to set email alerts
|

Media Coverage of Firms: Background, Integration, and Directions for Future Research

Abstract: Over the past years, media coverage of firms has received significant scholarly attention. However, the resulting literature is spread across multiple disciplines and, therefore, varies with regard to its theoretical underpinnings and contextual settings. This makes it challenging for scholars to understand the contributions of this literature, to identify areas of inquiry, and to develop an encompassing research agenda. In this review, we address these issues by surveying the diverse literature on media cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(87 citation statements)
references
References 156 publications
(483 reference statements)
4
80
0
Order By: Relevance
“…Our method is modeled after recently published Journal of Management reviews (e.g., Foss & Saebi, 2017; Graf-Vlachy, Oliver, Banfield, König, & Bundy, 2020; Saebi, Foss, & Linder, 2019). We restricted our review to articles that contained the term “organi* improvi*” in the title, abstract, or keywords.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our method is modeled after recently published Journal of Management reviews (e.g., Foss & Saebi, 2017; Graf-Vlachy, Oliver, Banfield, König, & Bundy, 2020; Saebi, Foss, & Linder, 2019). We restricted our review to articles that contained the term “organi* improvi*” in the title, abstract, or keywords.…”
Section: Methodsmentioning
confidence: 99%
“…This gleaning process narrowed the list to 173 articles. Finally, we employed a snowball search protocol similar to that of Graf-Vlachy et al (2020) and identified 13 additional articles to be included in our review. Thus, the final sample consists of 186 manuscripts.…”
Section: Methodsmentioning
confidence: 99%
“…With respect to innovation output, scholars should utilize recent developments in text‐mining and data‐mining techniques to develop more nuanced measures of innovation output. For example, scholars could try to capture the public's perceptions of firms' innovativeness through semantic analyses of press coverage (Graf‐Vlachy, Oliver, Banfield, König, & Bundy, 2020), sentiment analyses of social media data (Gautam & Yadav, 2014), or analyses of company rankings (e.g., Forbes, 2018). Alternative ways of determining the quantity and quality of newly developed products, services, and processes could include systematic analyses of trademark filings (Castaldi, 2020), the content and structure of company websites (Mirończuk & Protasiewicz, 2020) or mission statements (Hanisch, Haeussler, Graf‐Vlachy, König, & Cho, 2018), firms' 10‐K filings (Hoberg & Phillips, 2016), or analyst reports (Bellstam, Bhagat, & Cookson, 2020).…”
Section: An Agenda For Future Researchmentioning
confidence: 99%
“…We used newspaper articles because they provide comparable information through time and across countries (Duriau, Reger, & Pfarrer, 2007) and are a credible and legitimate source of information in research adopting an institutional perspective (Graf-Vlachy, Oliver, Banfield, König, & Bundy, 2019). Their use ensures the availability of comparable data that is independent of the access to informants (Duriau et al, 2007), which is difficult given the secrecy of family offices (Decker & Lange, 2013;Decker & Günther, 2016;Eigenheer, 2014;Glucksberg & Burrows, 2016).…”
Section: Datamentioning
confidence: 99%
“…They reflect the dynamics of stakeholders' perceptions of family offices in their institutional contexts and the evolution of these contexts. Their bias reflects their core readers' interests, journalists' attitudes, and sources of information (Graf-Vlachy et al, 2019;Hoffman, 1999;von Bloh et al, 2019).…”
Section: Datamentioning
confidence: 99%